ACCESSING CHILDREN’S IDEAS OF THE NATURALWORLD: AN EXPLORATION - KAUR, GURJEET (THE PRIMARY TEACHER, 2013)
The paper begins by examining different terms used to describe a variety of learners’ ideas. The almost similar terms like concepts, conceptions; alternative conceptions, misconceptions are dwelt upon. The paper then goes on to describe the different approaches that cognitive researchers have adopted to understand the learners’ thought processes in varying contexts. Most studies that have examined the alternative conceptions in different areas have attempted to categorise them. Some have tried to arrange these ideas in a hierarchical order based on their level of sophistication. Others have only juxtaposed these ideas into lateral categories, treating them as different ways of interpreting reality. Such attempts to impose order upon and look for similar patterns in the thinking processes of the students have then been discussed. Once the ideas have been accessed, the next step is to analyse them for any deviation from contemporary shared understanding and reflect upon the significance of these ideas in planning the course of further interactions with the learners. This has been attempted towards the end.